Composite particles, negative electrode for secondary battery, and secondary battery
Patent Information
- Application Number
- JP2024529985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-10-19
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-10-19
AI Technical Summary
【0014】 本発明によれば、膨張が抑制され、重要な性質の一つであるサイクル特性に優れた二次電池を与える複合粒子、前記複合粒子を有する二次電池用負極および前記二次電池用負極を有する二次電池が提供される。
Smart Images

Figure 0007632756000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite particle, a secondary battery negative electrode containing the composite particle, and a secondary battery containing the secondary battery negative electrode. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries are used in portable devices, hybrid and electric vehicles, home storage batteries, and the like, and are required to have a good balance of multiple properties such as electric capacity, safety, and operational stability. As such a secondary battery, lithium ion batteries are known that use a lithium intercalation compound that releases lithium ions from between layers as the negative electrode active material. For example, various lithium ion batteries that use a carbon material such as graphite that can absorb and release lithium ions between layers between crystal planes during charging and discharging as the negative electrode active material have been developed and are already in practical use.
[0003] Compared with carbon materials, silicon has a large theoretical electric capacity, so the use of silicon as an anode active material has been considered for the purpose of increasing the capacity of lithium-ion secondary batteries. However, silicon has a large difference between volume expansion and contraction during repeated charging and discharging, and silicon particles are destroyed during repeated charging and discharging. As a result, there is a demand for improving the cycle characteristics of secondary batteries using silicon as the anode active material.
[0004] As a method for suppressing the volumetric change of silicon and improving the cycle characteristics of a secondary battery, a method of buffering the volumetric change of silicon by forming voids has been proposed. For example, Patent Document 1 describes a battery negative electrode material that includes a silicon material region and a carbon material region made of a carbon material formed around the silicon material region at least partially with a gap therebetween, and the (002) average layer spacing d002 of the carbon material region is 0.365 nm or more and 0.390 nm or less as determined by powder X-ray diffraction using Cu-Kα radiation. It is described that the configuration of Patent Document 1 efficiently suppresses the expansion and contraction of silicon during charging and discharging, resulting in a secondary battery with improved specific capacity and cycle durability.
[0005] Patent Document 2 discloses a method for producing a composite material in which silicon is deposited in the pore volume of a porous scaffold material. Examples of the porous scaffold material include porous carbon materials having micropores, mesopores, or macropores.
[0006] Patent Document 3 describes composite particles for an energy storage device cell, each composite particle including biomass-derived carbon and an active material, and describes that the biomass-derived carbon is porous.
[0007] Also, a method has been proposed in which silicon having voids is used to suppress volumetric changes in the silicon and improve the cycle characteristics of a secondary battery. Patent Document 4 discloses silicon alloy particles that can produce porous silicon particles that undergo little change in volume even when Li ions are absorbed. Patent Document 5 discloses a particulate material consisting of a plurality of porous particles containing an electroactive material selected from silicon, germanium, or a mixture thereof, the particle material having a specific range of D50 particle size, intra-particle porosity, and pore size distribution measured by mercury porosimetry. It is described that the particulate material is an electroactive material that can be used to improve the charge / discharge capacity of a lithium-ion battery.
[0008] Patent Document 6 discloses a negative electrode active material that includes secondary particles including a first particle that is a primary particle, the first particle including a first core and a first surface layer that is disposed on the surface of the first core and includes carbon, the first core including at least one of silicon and a silicon compound, and a metal compound, the metal compound including at least one of a metal oxide and a metal silicate, and it is described that the first core and the second core are porous cores including a large number of pores. It is described that when the first core is a porous core, the diffusion of lithium ions proceeds quickly, whereas when the second core is a porous core, the diffusion of lithium ions proceeds quickly and the volume expansion of the second core during charging and discharging is suppressed. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2019-125435 A [Patent Document 2] JP 2020-514231 A [Patent Document 3] JP 2022-500822 A [Patent Document 4] Patent Publication No. 2021-167457 [Patent Document 5] JP 2017-533533 A [Patent Document 6] JP 2019-508842 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, even if voids are provided in the negative electrode active material to buffer the expansion as in Patent Documents 1 to 6, the cycle characteristics tend to decrease. Silicon oxycarbide has been attracting attention as an active material that combines high capacity with good cycle performance. Silicon oxycarbide is known to have a lower volume expansion rate due to lithium absorption than silicon and silicon oxide, and to exhibit stable cycle performance.
[0011] The inventors focused on the combination of silicon particles and silicon oxycarbide, and conducted various studies with the aim of efficiently suppressing the expansion and contraction of the volume of silicon that occurs during charging and discharging, improving the cycle characteristics of secondary batteries, and reducing the expansion of battery cells, which led to the completion of the present invention. That is, an object of the present invention is to provide composite particles which provide a secondary battery having low expansion and excellent cycle characteristics, which are important properties for a secondary battery. [Means for solving the problem]
[0012] The present invention has the following aspects. [1] Composite particles comprising silicon particles and a matrix phase containing Si, O, and C, having one or more voids, and having an average porosity calculated by the following formula (1) of 1% or more and 80% or less. Porosity (%) = (total pore volume / (specific volume + total pore volume)) × 100 (1) [2] The composite particle according to [1], having voids inside the silicon particle or at the interface between the silicon particle and the matrix phase. [3] The composite particle according to [1] or [2], wherein the porosity of the silicon particle having voids therein, calculated from the formula (1), is 10% or more and 80% or less. [4] The composite particle according to any one of [1] to [3], wherein a gap larger than 0 nm and smaller than 100 nm exists between the surface of at least one silicon particle and the matrix phase. [5] The composite particle according to any one of [1] to [4], wherein the porosity of the matrix phase calculated from the formula (1) is 20% or less. [6] The composite particle according to any one of [1] to [5], wherein the silicon element content is 20% by mass or more and 80% by mass or less. [7] A composite particle according to any one of [1] to [6], comprising nanosilicon particles having a particle diameter of 1000 nm or less. [8] The composite particle according to any one of [1] to [7], wherein the matrix phase contains at least silicon oxycarbide and a carbonaceous layer.
[0013] Further, the present invention has the following aspects. [9] A negative electrode for a secondary battery comprising the composite particles according to any one of [1] to [8].
[10] A secondary battery comprising the negative electrode for secondary batteries according to [9]. Effect of the Invention
[0014] According to the present invention, there are provided composite particles which provide a secondary battery in which expansion is suppressed and which has excellent cycle characteristics, which is one of its important properties; a secondary battery negative electrode having the composite particles; and a secondary battery having the secondary battery negative electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In the following description, Si represents the same substance as "silicon", O represents the same substance as "oxygen", C represents the same substance as "carbon", and N represents the same substance as "nitrogen". The composite particle of the present invention (hereinafter also referred to as "the present composite particle") contains silicon particles and a matrix phase containing Si, O, and C, has one or more voids, and has an average porosity calculated by the following formula (1) of 1% or more and 80% or less. Porosity (%) = (total pore volume / (specific volume + total pore volume)) × 100 (1)
[0016] As mentioned above, silicon particles have a high capacity, but a large volume change occurs due to the absorption and release of a large amount of lithium ions, which is thought to result in poor cycle characteristics. Therefore, a method has been proposed in which voids are provided between the silicon particles and / or the matrix phase, and the voids buffer the volume expansion and suppress the destruction of the carbon coating. However, if the voids are not appropriate, the buffer effect does not function sufficiently, and the amount of SEI (Solid Electrolyte Interface) is increased due to the increase in surface area caused by cracks in the active material, which is thought to reduce the initial Coulombic efficiency.
[0017] The voids proposed so far do not have a sufficient buffering effect, and there are cases where the improvement of cycle performance is still insufficient. As a result of examining the reason, the present inventors concluded that the conventional voids alone are not sufficient to alleviate the expansion of silicon particles and the associated expansion of active materials, or that even if voids exist, the voids are not fully utilized, and therefore, the formation of appropriate voids that can fully alleviate the expansion of active materials was examined. Furthermore, various evaluations were conducted to evaluate whether the formed voids can fully alleviate the expansion of silicon particles and the associated expansion of active materials.
[0018] As a result, the present inventors have found that the porosity defined by the above formula (1) may represent voids that can sufficiently mitigate the expansion of silicon particles and the associated expansion of the active material. Furthermore, by using silicon oxycarbide, which has superior mechanical properties compared to conventionally used carbon, as the matrix, the composite particles have a strong expansion suppression effect and the porous structure is less likely to collapse with repeated charging and discharging. As a result, it was found that the expansion of the silicon particles is further suppressed, and the formed voids are fully utilized to buffer the expansion of the silicon particles, thereby suppressing the expansion of the entire composite particle containing silicon particles and silicon oxycarbide.
[0019] From the above study results, it was found that the present composite particles have a buffering effect capable of sufficiently mitigating the expansion of silicon particles, and furthermore, the expansion of silicon particles is suppressed, and the expansion rate of the entire composite particle is also suppressed. Furthermore, it was found that a secondary battery using a secondary battery negative electrode containing the present composite particles combined with silicon oxycarbide, which has a porosity defined by the above formula (1) within a specific range, has improved cycle characteristics. This effect is believed to be due to the present composite particles having high pressure resistance and the appropriate control of the voids effectively buffering the volume expansion and contraction during charging and discharging, thereby improving the cycle characteristics of the secondary battery.
[0020] The silicon particles contained in the present composite particle are particles of zero-valent silicon, and the average particle size is preferably from 1 nm to 1000 nm, more preferably from 5 nm to 500 nm, and even more preferably from 10 nm to 200 nm.
[0021] Here, the average particle size refers to the volume average particle size, and is the D50 value measured by dynamic light scattering using a laser diffraction particle size analyzer, etc. D50 is the particle size at which the cumulative volume distribution curve of silicon particles reaches 50% of the total when the cumulative volume distribution curve is drawn from the small diameter side.
[0022] The silicon particles having a large size become large lumps, and when the composite particles are used as the negative electrode active material to form a negative electrode for a secondary battery, the capacity retention rate of the negative electrode active material is likely to decrease because the pulverization phenomenon is likely to occur during charging and discharging. On the other hand, the silicon particles having a small size of less than 10 nm are too fine, so the silicon particles tend to aggregate with each other. Therefore, the dispersibility of the silicon particles in the composite particles may decrease. In addition, if the silicon particles are too fine, their surface activity energy increases, and there is a tendency for by-products and the like to increase on the surface of the silicon particles during high-temperature sintering of the negative electrode active material. These may lead to a decrease in charge and discharge performance. From this viewpoint, it is preferable that the silicon particles are within the above-mentioned range of average particle size, and that the number of large silicon particles exceeding 1000 nm and small silicon particles less than 10 nm, for example, is as small as possible.
[0023] From the viewpoint of suppressing expansion due to repeated charging and discharging, the silicon particles preferably contain nanosilicon particles having a particle diameter of 1000 nm or less, and more preferably contain nanosilicon particles having a particle diameter of 500 nm or less. When the silicon particles contain nanosilicon particles having a particle diameter of 1000 nm or less, the content is preferably 20 mass% or more, and more preferably 25 mass% or more, with the mass of the entire silicon particles including the nanosilicon particles being 100 mass%.
[0024] The silicon particles can be produced by granulating silicon chunks by crushing, etc. The presence of these silicon particles can improve the charge / discharge capacity and initial coulombic efficiency when the composite particles are used in a secondary battery. The silicon particles can be obtained by, for example, pulverizing a block of zero-valent silicon to obtain particles having an average particle size in the above-mentioned range. Examples of the mill used for pulverizing the silicon chunks to produce silicon particles include a ball mill, a bead mill, a jet mill, etc. The pulverization may be wet pulverization using an organic solvent, and the organic solvent may be, for example, an alcohol or a ketone, but may also be an aromatic hydrocarbon solvent such as toluene, xylene, naphthalene, or methylnaphthalene. The obtained silicon particles can be adjusted to a desired average particle size by controlling the bead mill conditions such as bead particle size, blending ratio, rotation speed, or grinding time, and by classification or the like.
[0025] The shape of the silicon particles is not particularly limited, but examples thereof include a spherical shape, a sheet shape, and a flat shape.
[0026] The specific surface area of the silicon particles is 100 m from the viewpoint of capacitance and initial coulombic efficiency. 2 / g to 1500m 2 / g is preferred. The specific surface area of a silicon particle is 100 m2 in terms of capacitance and initial coulombic efficiency. 2 / g to 1000m 2 / g is more preferable, and 100m 2 / g to 500m 2 / g is more preferred. The specific surface area is a value determined by the BET method, and can be determined by nitrogen gas adsorption measurement, for example, by using a specific surface area measuring device. The specific surface area of silicon particles can be measured as follows: The amount of nitrogen adsorption at liquid nitrogen temperature and a relative pressure of 0.5 or less is determined at multiple points, and the specific surface area is calculated from a BET plot in the range where the heat of adsorption C value is positive and highly linear.
[0027] The shape of silicon particles may be granular, needle-like, or flake-like, but is preferably crystalline. When silicon particles are crystalline, the crystallite diameter obtained from the diffraction peak attributed to Si(111) in X-ray diffraction is preferably in the range of 5 nm to 30 nm from the viewpoint of initial coulombic efficiency and capacity retention. The crystallite diameter is more preferably 25 nm or less, and even more preferably 20 nm or less.
[0028] The present composite particle has a matrix phase containing Si, O, and C. From the viewpoint of obtaining an advantageous balance between charge / discharge performance and capacity retention rate when the present composite particle is used as a secondary battery, the content ratio of O to Si in the matrix phase is preferably 0.1 or more and 2 or less, more preferably 0.1 or more and 1.5 or less, even more preferably 0.1 or more and 1.0 or less, and particularly preferably 0.1 or more and 0.7 or less.
[0029] From the viewpoint of the balance between charge / discharge performance and initial coulombic efficiency when the composite particles are used in a secondary battery, the C to Si content in the matrix phase is preferably 0.3 to 11, more preferably 0.3 to 8. The above content ratios are the molar ratios of Si, O, and C contained in the composite particles, and the content ratio of O to Si is the number of moles of O contained in the composite particles per mole of Si contained in the matrix phase. Similarly, the content ratio of C to Si is the number of moles of C contained in the matrix phase per mole of Si contained in the matrix phase.
[0030] From the viewpoint of the balance between the charge / discharge capacity, the initial coulombic efficiency, and the capacity retention rate, the sum of the content ratio of O to Si and the content ratio of C to Si is preferably 1.2 or more, and more preferably 2.3 or more.
[0031] These content ratios can be calculated by measuring the content of each element and then converting it into a molar ratio (atomic number ratio). In this case, the O and C contents can be quantified using an inorganic elemental analyzer, and the Si content can be quantified using an inductively coupled plasma optical emission spectrometer (ICP-OES). Although the content ratio is preferably measured by the above-mentioned method, it is also possible to perform local analysis of the composite particle, obtain the content ratio data obtained by the analysis at many measurement points, and infer the content ratio of the entire composite particle. Examples of local analysis include energy dispersive X-ray spectroscopy (SEM-EDX) and electron probe microanalyzer (EPMA).
[0032] The matrix phase containing Si, O, and C is preferably a three-dimensional network structure of a silicon oxycarbide (hereinafter also referred to as "SiOC") skeleton (hereinafter also referred to as "SiOC skeleton"), and is preferably a matrix having a carbonaceous phase composed only of C element together with the SiOC skeleton structure. The carbonaceous phase referred to here means C that is not contained in the three-dimensional skeleton of SiOC, and includes carbon that exists as free carbon, carbon that is bonded between C in the carbonaceous phase, and C that bonds the SiOC skeleton and the carbonaceous phase.
[0033] As described below, the matrix phase preferably contains silicon oxycarbide and a calcined product of a carbon source resin, and more preferably contains silicon oxycarbide and a calcined product of a phenol resin.
[0034] The SiOC skeleton in the matrix phase that constitutes the composite particles has the characteristic of high chemical stability, and the composite structure with the carbonaceous phase reduces the electronic transition resistance and facilitates the diffusion of lithium ions. The silicon particles are tightly wrapped in the composite structure of the SiOC skeleton and the carbonaceous phase, preventing direct contact between the silicon particles and the electrolyte. Therefore, the negative electrode active material containing the composite particles contains silicon particles that play a role as a main component for the expression of charge / discharge performance, while preventing chemical reactions between silicon and the electrolyte during charge / discharge to the maximum extent possible, thereby preventing the performance degradation of the silicon particles.
[0035] More specifically, when lithium ions approach SiOC, the electron distribution inside the SiOC changes, forming electrostatic bonds and coordinate bonds between the SiOC and the lithium ions, and the lithium ions are stored in the SiOC framework. The energy of these coordinate bonds is relatively low, so the lithium ion desorption reaction occurs easily. In other words, it is believed that SiOC can reversibly cause lithium ion insertion and desorption reactions during charging and discharging.
[0036] The matrix phase contained in the present composite particle may contain nitrogen atoms (hereinafter also referred to as "N") in addition to the above-mentioned Si, O, and C. N can be introduced into the present composite particle by forming atomic groups containing N as functional groups in the molecules of raw materials used in the method for producing the present composite particle described below, such as phenolic resins, dispersants, polysiloxane compounds, other nitrogen compounds, and nitrogen gas used in the firing process. By containing N, the present composite particle tends to have excellent charge / discharge performance and capacity retention when used as a negative electrode active material. When the present composite particle contains N, the N content is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and even more preferably 1 mass % or more, based on the total mass of Si, O, C and N being 100 mass %, from the viewpoints of charge / discharge performance and capacity retention rate. Moreover, from the viewpoint of charge / discharge performance and capacity retention rate, the content is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0037] The composite particle has one or more voids, and the porosity calculated by the following formula (1) is 1% or more and 80% or less. Porosity (%) = (total pore volume / (specific volume + total pore volume)) × 100 (1) As long as the porosity of the composite particle calculated by the formula (1) is within the above range, the voids may be present anywhere in the composite particle, and for example, it is preferable that the voids are present within the silicon particle, at the interface between the silicon particle and the matrix phase, or within the matrix phase. The voids may be present in one or more of these locations.
[0038] In the above formula (1), the total pore volume is the sum of the volumes of all the pores, and is calculated by converting the amount of gas adsorbed by the adsorbate at any relative pressure into the volume of the adsorbate in a liquid state. The unit is usually volume per unit mass, cm 3 It is expressed in / g.
[0039] The total pore volume of the composite particles can be calculated, for example, by image analysis using SEM observation, mercury intrusion porosimetry, or a specific surface area meter. Among these calculation methods, the method of calculation using a specific surface area meter is preferred from the viewpoint of accuracy. When the total pore volume is measured using a specific surface area meter, the pores present inside the particles may not be measured. Therefore, when measuring the total pore volume, the composite particles are crushed, and the pores present inside the particles are exposed to the surface, and then the specific surface area meter is used to measure the total pore volume of the composite particles as accurately as possible. When the composite particles are crushed in measuring the total pore volume, the composite particles are preferably crushed until the average particle diameter of the composite particles after crushing is 2.0 μm to 1.0 μm in D50, and more preferably until the average particle diameter is 1.0 μm to 0.5 μm.
[0040] In the above formula (1), the specific volume is the volume per unit mass of the composite particle excluding the pores and the concave portions on the surface, and is calculated from the reciprocal of the true density. The unit of the specific volume is usually the volume per unit mass, cm 3 It is expressed in / g. The true density can usually be measured by a true density meter.
[0041] The definition of the porosity according to the above formula (1) is the value obtained by dividing the volume of the voids, including the internal pores and surface recesses, of the present composite particle by the apparent volume, including the pores and surface recesses of the present composite particle. In other words, since the voids include the internal pores and surface recesses, it is considered to be a more accurate porosity than the conventional definition of porosity. As described below, the volume of voids is measured by exposing the pores present inside the particle to the surface, so that the volume can be measured accurately even if the pores inside have complex shapes. Furthermore, since the voids throughout the entire particle, including the surface depressions, can be measured evenly and consistently, it is believed that the size of the voids in composite particles can be evaluated more accurately. Since the porosity defined by the above formula (1) is the value obtained by dividing the more accurate volume of the composite particle measured as described above by the apparent volume of the composite particle, the obtained porosity is considered to be a value that more accurately reflects the actual state of the composite particle.
[0042] When the voids are present within the silicon particles, the porosity of the silicon particles is calculated by the formula (1), and from the viewpoint of improving cycle characteristics during charging and discharging, the value is preferably 80% or less, and more preferably 70% or less. From the viewpoint of suppressing expansion during charging and discharging, the porosity of the silicon particles calculated by the formula (1) is more preferably 1% or more, even more preferably 5% or more, and particularly preferably 10% or more.
[0043] The porosity of the silicon particles can be calculated in the same manner as in the calculation of the porosity of the present composite particles, whereby the total pore volume can be measured, for example, using a specific surface area meter, and the true density can usually be measured with a true density meter. In addition, when measuring the total pore volume, it is preferable to crush the silicon particles, expose the pores present inside the particles to the surface, and then measure using a specific surface area meter, as in the case of the present composite particles. When crushing the silicon particles in measuring the total pore volume, it is preferable to crush the silicon particles after crushing until the average particle size D50 is 1000nm to 500nm, and more preferably 500nm to 10nm.
[0044] When the voids are at the interface between the silicon particles and the matrix phase, from the viewpoint of expansion suppression, it is preferable that there be a void greater than 0 and not greater than 100 nm from the surface of at least one silicon particle in the composite particle. When the voids are at the interface between the silicon particles and the matrix phase, it is more preferable that there be a void of 5 nm or more from the surface of at least one silicon particle in the composite particle, and even more preferable that there be a void of 10 nm or more from the surface of at least one silicon particle in the composite particle, from the viewpoint of expansion suppression. Furthermore, when the voids are at the interface between the silicon particles and the matrix phase, from the viewpoint of cycle characteristics, it is more preferable that there be voids of 100 nm or less from the surface of at least one silicon particle in the composite particle, and it is even more preferable that there be voids of 80 nm or less.
[0045] The voids at the interface between the silicon particles and the matrix phase can be measured by electron microscopy and elemental distribution analysis, which allows the distance at which the silicon particle / matrix interface exists to be calculated using image analysis software.
[0046] When the voids are present in the matrix phase, the void ratio in the matrix phase is calculated by the formula (1), and from the viewpoint of cycle characteristics, the value is preferably 20% or less. From the viewpoint of cycle characteristics, the void ratio in the matrix phase calculated by the formula (1) is more preferably 15% or less, and further preferably 10% or less. When the voids are present in the matrix phase, the void ratio in the matrix phase calculated by the formula (1) is more preferably 0.05% or more, and even more preferably 0.1% or more, from the viewpoint of suppressing expansion.
[0047] The porosity in the matrix phase can be calculated by, for example, measuring the specific surface area after removing the silicon particles from the composite particles to leave only the matrix phase, and the true density can usually be measured by a true density meter. Alternatively, as shown in the examples, the matrix phase alone without adding silicon particles can be prepared, and the porosity of the matrix phase can be measured in the same manner as above. Alternatively, from an SEMM image of an arbitrary cross section of a composite particle having a silicon particle and a matrix phase, the proportion of clear areas in any five areas excluding the Si particle area may be binarized using image analysis software, and the porosity within the matrix phase may be calculated.
[0048] In addition, when measuring the total pore volume, it is preferable to crush only the matrix phase excluding the silicon particles, as in the case of the present composite particles, to expose the pores present inside the matrix phase to the surface, and then measure using a specific surface area meter. When crushing the matrix phase in measuring the total pore volume, it is preferable to crush the matrix phase until the average particle size after crushing is 2.0 μm to 1.0 μm in D50, and more preferably 1.0 μm to 0.1 μm.
[0049] The porosity of the composite particles can be set within the above range by appropriately selecting the porosity within the silicon particles, the voids at the interface between the silicon particles and the matrix phase, and the porosity within the matrix phase. More specifically, the porosity of the composite particles finally obtained can be set within the above range by setting the porosity within the silicon particles, the voids at the interface between the silicon particles and the matrix phase, and the porosity within the matrix phase within the above range.
[0050] The composite particles preferably have a structure in which silicon particles are uniformly dispersed in a matrix phase having a three-dimensional network structure of a SiOC skeleton composed of the elements Si, O, and C. The matrix phase more preferably has a composite structure with the carbonaceous phase.
[0051] The amount of silicon element contained in the present composite particle is preferably 20% by mass or more and 80% by mass or less, and more preferably 30% by mass or more and 70% by mass or less, based on 100% by mass of the total mass of the silicon particles and the matrix phase, from the viewpoint of improving the expansion coefficient during charge and discharge and the cycle characteristics. The amount of silicon element in the present composite particles can be determined, for example, by ICP measurement.
[0052] The specific surface area of this composite particle is 0.01m 2 / g to 50m2 From the viewpoints of the amount of solvent absorbed during electrode preparation and the amount of binder used to maintain binding properties, the specific surface area of the composite particles is preferably 0.1 m 2 / g or more is preferable, and 1m 2 / g or more. The specific surface area of the composite particles is preferably 40 m 2 / g or less is preferable, and 30m 2 / g or less is more preferable. The specific surface area of the composite particles is a value determined by the BET method. The nitrogen adsorption amount is determined at multiple points at a relative pressure of 0.5 or less at liquid nitrogen temperature, and the specific surface area can be calculated from the range in which the heat of adsorption C value is positive and highly linear from the BET plot.
[0053] The average particle diameter of the composite particles is preferably 0.5 μm to 20 μm, more preferably 2 μm to 15 μm. If the average particle diameter is too small, the specific surface area increases significantly, and when used as a secondary battery, the reversible charge / discharge capacity per unit volume may decrease due to an increase in the amount of SEI generated during charging and discharging. If the average particle diameter is too large, there is a risk of peeling off from the current collector during the preparation of the electrode film. As described above, the average particle diameter is the volume average particle diameter, and is the value of D50. The method for measuring D50 is the same as described above. The particle size range of the composite particles before classification is preferably 0.1 μm to 30 μm, and the particle size range after removal of fine particles is preferably 0.5 μm to 30 μm. The composite particles may be in the form of any of granules, needles, and flakes.
[0054] The composite particles are 29 It is preferable that the chemical shift value obtained from the Si-NMR spectrum satisfies the following formula. 0.05 In the above formula, A is the area intensity of the peak attributable to Si (0 valence) in the range of -70 ppm to -90 ppm, and B is SiO 4 The area intensity of the peaks in the range of -90 ppm to -130 ppm assigned to the bond is shown.
[0055] In the three-dimensional network structure of the SiOC skeleton, the bonds can be divided into three main types based on the type of O or C atom that bonds with Si and the number of bonds with each atom. The domains with the three types of bonds are SiO 2 C 2 , SiO 3 C, and SiO 4 These domains are further randomly bonded to form silicon oxycarbide (SiOC). 3 The chemical shift (solid-state NMR) of the C domain is in the range of −60 ppm to −80 ppm with the center position at −70 ppm.
[0056] In the present composite particle, 29 The fact that the chemical shift value obtained from the Si-NMR spectrum satisfies the range of A / B indicates that the SiO 2 present in the silicon oxycarbide and the silicon particles having a valence of zero in the present composite particle are 4 The ratio A / B is a ratio at which the silicon particles are likely to exhibit their performance, and when used in a secondary battery, the battery has excellent charge / discharge performance, particularly cycle characteristics. The ratio A / B is more preferably in the range of 0.8≦A / B≦2.9, and even more preferably in the range of 0.9≦A / B≦2.8.
[0057] 29 The Si-NMR spectrum can be easily obtained using a solid-state NMR device. In this specification, the solid-state NMR measurement is performed using, for example, a device (JNM-ECA600) manufactured by JEOL Co., Ltd. The A / B is obtained by performing a single pulse measurement with an 8 mm probe after 10 minutes of tuning with a solid-state NMR analyzer, Fourier transforming the obtained solid-state NMR spectrum data (accumulated 64 times), and performing waveform separation using the Gauss+Lorentz function. Next, based on the peak area obtained by waveform separation, the ratio of the area intensity, A, of the peak in the range of -70 ppm to -90 ppm to the area intensity, B, of the peak in the range of -90 ppm to -130 ppm is calculated.
[0058] In the infrared analysis of this composite particle, -1From 2200cm -1 It is preferable that there is no absorption spectrum due to the Si-H stretching vibration at 2000 cm -1 From 2200cm -1 If there is no absorption spectrum due to the Si-H stretching vibration in the material, it means that lithium ions can be efficiently absorbed, which leads to an improvement in the charge / discharge capacity. The absence of absorption spectrum due to Si-H stretching vibration is due to the absence of absorption spectrum at 900 cm -1 From 1200cm -1 For the absorption intensity in the range of 2000cm -1 From 2200cm -1 The absorption intensity of the absorption spectrum derived from the Si-H stretching vibration in is 0.1% or less, and more preferably 0.05% or less.
[0059] When the matrix phase of the composite particle has the carbonaceous phase, in the Raman spectrum of the carbonaceous phase, the carbon structure has a peak at 1590 cm assigned to the G band of the graphite long-period carbon lattice structure. -1 Scattering peaks near 1330 cm, which are assigned to the D band of the disordered and defective graphitic short-period carbon lattice structure, -1 It is preferable that the carbonaceous phase has scattering peaks around G band and D band, and the scattering peak intensity ratio I (G band / D band) is in the range of 0.7 to 2. The scattering peak intensity ratio I is more preferably 0.7 to 1.8. The fact that the scattering peak intensity ratio I is in the above range means that the following can be said about the carbonaceous phase in the matrix.
[0060] Some of the C atoms in the carbonaceous phase are bonded to some of the Si atoms in the SiOC skeleton. This carbonaceous phase is an important component that affects the charge / discharge characteristics. The carbonaceous phase is mainly composed of SiO 2 C 2 ,SiO 3 C, and SiO 4The carbonaceous phase is formed in the SiOC skeleton, which is composed of the carbonaceous phase and the active material. Because the carbonaceous phase is bonded to some of the Si atoms in the SiOC skeleton, electron transfer becomes easier between the Si atoms inside the SiOC skeleton and on the surface and the free carbon. This makes it possible to rapidly insert and extract lithium ions during charging and discharging when used as a secondary battery, improving the charge and discharge characteristics. In addition, the composite particles may expand and contract due to the insertion and extraction reactions of lithium ions, but the presence of the carbonaceous phase in their vicinity is thought to mitigate the expansion and contraction of the entire active material, greatly improving the capacity retention rate.
[0061] The carbonaceous phase is preferably formed by pyrolysis of the silicon-containing compound and the carbon source resin, which are precursors, in an inert gas atmosphere when the composite particles are produced. Specifically, the carbonizable sites in the molecular structures of the silicon-containing compound and the carbon source resin are converted into carbon components by high-temperature pyrolysis in an inactive atmosphere, and some of these carbons are bonded to a part of the SiOC skeleton. The carbonizable components are preferably hydrocarbons, more preferably alkyls, alkylenes, alkenes, alkynes, and aromatics, and even more preferably aromatics.
[0062] In addition, the presence of free carbon as the carbonaceous phase is expected to reduce the resistance of the composite particles, and when used in the negative electrode of a secondary battery, the reaction inside the negative electrode active material occurs uniformly and smoothly, resulting in a secondary battery material with an excellent balance between charge / discharge performance and capacity retention. Although free carbon can be introduced only from a Si-containing compound, the use of a carbon source resin in combination is expected to increase the amount of free carbon present and its effect. The type of carbon source resin is preferably, for example, a carbon compound containing a six-membered carbon ring.
[0063] The state of the carbonaceous phase can be identified by a thermogravimetric differential thermal analyzer (TG-DTA) in addition to the Raman spectrum. Unlike the C atoms in the SiOC skeleton, the carbonaceous phase is easily decomposed in the atmosphere, and the amount of carbon present can be determined by the amount of thermal weight loss measured in the presence of air. In other words, the amount of carbon can be quantified by using TG-DTA. In addition, the changes in the thermal decomposition temperature behavior, such as the decomposition reaction start temperature, the decomposition reaction end temperature, the number of thermal decomposition reaction species, and the temperature of the maximum weight loss amount for each thermal decomposition reaction species, can be easily understood by the thermal weight loss behavior from the above measurement. The state of carbon can be determined using the temperature values of these behaviors. On the other hand, the C atoms in the SiOC skeleton, i.e., the SiO 2 C 2 , SiO 3 C, and SiO 4 The carbon atoms bonded to the silicon atoms that compose the carbon phase have a very strong chemical bond, making them highly thermally stable and unlikely to be thermally decomposed in air within the measurement temperature range of the thermal analyzer. In addition, the carbon in the carbonaceous phase has properties similar to those of amorphous carbon, so it is thermally decomposed in air at temperatures between about 550°C and 900°C. As a result, a rapid weight loss occurs. The maximum temperature for the TG-DTA measurement conditions is not particularly limited, but in order to completely complete the thermal decomposition reaction of carbon, it is preferable to perform the TG-DTA measurement in the atmosphere under conditions of about 25°C to about 1000°C or higher.
[0064] The true density of this composite particle is 1.6 g / cm 3 Higher than 2.4g / cm 3 Less than 1.7 g / cm is preferred. 3 Higher than 2.35g / cm 3 When the true density is within the above range, the composition ratio of each component constituting the composite particle and the porosity are within appropriate ranges, and when used as a negative electrode active material, charge / discharge performance is easily exhibited.
[0065] The composite particles may have a carbon coating. The carbon coating preferably covers at least a portion of the surface of the composite particle, and the carbon coating is preferably a coating made of low crystalline carbon. From the viewpoint of improving the chemical stability and thermal stability of the composite particle, the amount of the carbon coating is preferably 0.1% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and even more preferably 5% by mass to 20% by mass, based on 100% by mass of the composite particle including the carbon coating. Also, from the viewpoint of improving the chemical stability and thermal stability of the active material, the average thickness of the carbon coating is preferably 10 nm to 300 nm.
[0066] From the viewpoint of improving the chemical stability and thermal stability of the composite particles, it is preferable that 1% or more of the surface of the composite particles has a carbon coating, and more preferably 10% or more of the surface of the composite particles has a carbon coating. The composite particles may have a carbon coating continuously or discontinuously on their surfaces. The carbon coating is preferably formed on the surface of the composite particles by chemical vapor deposition.
[0067] From the viewpoint of improving electrical conductivity, the present composite particles preferably contain at least one element selected from the group consisting of Li, K, Na, Mg, Al, Fe, Ni, Ti and Bi. Among these elements, it is preferable to contain Li, Na, Mg, Al, Fe, Ni and Ti, and it is more preferable to contain Li, Na, Mg, Al, Fe and Ni.
[0068] The present composite particle may contain other components in addition to the silicon particles and matrix phase, as required.
[0069] The present composite particles can be produced, for example, by a method including the following steps 1 to 3. Step 1: A slurry of wet-milled silicon particles is mixed with a raw material that provides the matrix phase, stirred and dried to obtain a precursor. Step 2: The precursor obtained in step 1 is calcined in an inert atmosphere at a maximum temperature within the range of 1000° C. to 1180° C. to obtain a calcined product. Step 3: The fired product obtained in step 2 is pulverized to obtain the present composite particles.
[0070] Each step will be described below. <Process 1> The wet-milled silicon (0-valent) slurry used in step 1 can be prepared by pulverizing silicon particles in a wet powder mill using an organic solvent. A dispersant may be used to promote the pulverization of silicon particles in the organic solvent. The wet mill is not particularly limited, and examples of the wet mill include a roller mill, a high-speed rotary mill, a container-driven mill, and a bead mill. In the wet grinding, it is preferable to grind the silicon particles until they reach a desired average particle size.
[0071] The organic solvent used in the wet method is an organic solvent that does not chemically react with silicon. Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone; alcohols such as ethanol, methanol, normal propyl alcohol, and isopropyl alcohol; and aromatics such as benzene, toluene, and xylene.
[0072] The dispersant may be an aqueous or non-aqueous dispersant. In order to suppress excessive oxidation of the surface of silicon particles, it is preferable to use a non-aqueous dispersant. Examples of the non-aqueous dispersant include polymer types such as polyethers, polyalkylene polyamines, and polycarboxylic acid partial alkyl esters, low molecular types such as polyhydric alcohol esters and alkyl polyamines, and inorganic types such as polyphosphates. The concentration of silicon in the silicon (0-valent) slurry is not particularly limited, but when the solvent and, if necessary, a dispersant are included, the total amount of the dispersant and silicon particles is 100 mass%, and the amount of silicon particles is preferably in the range of 5 mass% to 40 mass%, more preferably 10 mass% to 30 mass%.
[0073] When the composite particles have voids in the silicon particles, a silicon slurry having voids may be used in step 1. Examples of methods for producing silicon particles having voids include the methods described in Patent Documents 4 and 5. They can also be produced by anodization. Anodization is a method for obtaining porous silicon by passing electricity through an aqueous hydrofluoric acid solution using a silicon anode. In this case, platinum is usually used as the cathode. When silicon particles having voids are obtained by anodization, the porosity can be controlled by the strength and duration of the electric current. They can also be produced by a solution process. The solution process is a method in which metal nanoparticles are formed on the surface of silicon particles, and the metal nanoparticles are etched with a hydrofluoric acid / hydrogen peroxide solution to obtain porous silicon. When porous silicon particles are obtained by the solution process, the porosity can be controlled by the treatment time and the concentration of hydrofluoric acid / hydrogen peroxide.
[0074] The raw material that provides the matrix phase used in the step 1 is preferably a synthetic resin or a natural chemical raw material that is carbonized by high-temperature firing in an inert atmosphere and has an aromatic functional group.
[0075] Examples of synthetic resins include thermoplastic resins such as polyvinyl alcohol and polyacrylic acid, and thermosetting resins such as phenol resin and furan resin. Examples of natural chemical raw materials include coke and heavy oil, particularly tar pitches such as coal tar, light tar oil, medium tar oil, heavy tar oil, naphthalene oil, anthracene oil, coal tar pitch, pitch oil, mesophase pitch, oxygen-crosslinked petroleum pitch, and heavy oil.
[0076] When the composite particles have voids in the matrix phase, an organic compound may be used in step 1. For example, this can be achieved by adding an organic compound such as a dispersant as a sacrificial phase when mixing with the raw material that provides the matrix phase, separate from the silicon slurry production. The void ratio can be controlled by adjusting the amount added. As the organic compound such as a dispersant, a compound having a phenyl group, such as a phenyl compound, and further having solubility in a polar solvent is preferable, and examples thereof include phenylalanine, salicylic acid, methyl salicylate, phthalic acid, maleic acid, quinone, benzoquinone, polyphenol, polystyrene, etc.
[0077] The raw material that gives the matrix phase and the silicon slurry are uniformly mixed and stirred, and then the mixture is desolvated and dried to obtain a precursor of the composite particle (hereinafter also referred to as "precursor"). The mixing is performed using a device that has a dispersing and mixing function. Examples of the device include a stirrer, an ultrasonic mixer, and a premix disperser. In the desolvation and drying process for the purpose of distilling off the organic solvent, a dryer, a reduced pressure dryer, a spray dryer, etc. can be used.
[0078] The precursor preferably contains 3% to 97% by mass of silicon particles which are silicon (valence 0) and 3% to 97% by mass of the solid content of the raw material which gives the matrix phase, and more preferably contains 20% to 80% by mass of the solid content of the silicon particles and 20% to 80% by mass of the solid content of the carbon source resin. By subjecting the precursor of the negative electrode active material to the heat treatment described later, the mass is reduced and the ratio of nanosilicon in the negative electrode active material may change, so the content of silicon particles in the precursor may be appropriately set based on the content of silicon particles in the intended composite particle.
[0079] <Process 2> In step 2, the precursor obtained in step 1 is fired in an inert atmosphere at a maximum temperature range of 1000°C to 1180°C, whereby the thermally decomposable organic components are completely decomposed, and the other main components are converted into a fired product suitable for the present composite particles by precisely controlling the firing conditions. Specifically, the raw materials that provide the matrix phase of the raw materials are partially converted into free carbon by the energy of the high-temperature treatment. In other words, a matrix phase containing the fired product of the raw materials that provide the matrix phase is obtained by firing. The fired product referred to here is a product in which the composition or structure of the organic compounds, such as the raw materials that provide the matrix phase, have been partially or completely changed due to decomposition or conversion at high temperatures. The fired material of the raw material that gives the matrix phase may have all of the raw material that gives the matrix phase converted to carbon, or may have a portion converted to carbon with the remainder maintaining the structure of the raw material that gives the matrix phase.
[0080] In step 2, the precursor obtained in step 1 is fired in an inert atmosphere according to a firing program defined by the heating rate, holding time at a constant temperature, etc. The maximum temperature is the highest temperature to be set, and it strongly influences the structure and performance of the fired product, the composite particle. In the present invention, the maximum temperature is set to 1000°C to 1180°C, so that the microstructure of the composite particle can be precisely controlled and oxidation of silicon particles due to firing at excessively high temperatures can be avoided, resulting in better charge / discharge characteristics.
[0081] The calcination method is not particularly limited, but it is sufficient to use a reaction device having a heating function in an inert atmosphere, and treatment can be performed by a continuous method or a batch method. The calcination device can be appropriately selected from a fluidized bed reaction furnace, a rotary furnace, a vertical moving bed reaction furnace, a tunnel furnace, a batch furnace, a rotary kiln, etc. depending on the purpose.
[0082] <Process 3> Step 3 is a step of obtaining the composite particles by pulverizing the fired product obtained in step 2 and classifying it as necessary. The pulverization may be performed in one step until the particle size reaches the desired particle size, or may be performed in several steps. For example, if the fired product is in the form of lumps or agglomerates of 10 mm or more, and composite particles of 10 μm are to be produced, the particles are coarsely pulverized with a jaw crusher, roll crusher, etc. to obtain particles of about 1 mm, then crushed to 100 μm with a glow mill, ball mill, etc., and pulverized to 10 μm with a bead mill, jet mill, etc. The particles produced by pulverization may contain coarse particles, and classification is performed to remove them, or to remove fine powder and adjust the particle size distribution. The classifier used is a wind classifier, a wet classifier, etc., depending on the purpose, but when removing coarse particles, a classification method that passes through a sieve is preferable because it can reliably achieve the purpose. In addition, if the precursor mixture is controlled to a shape near the target particle size by spray drying or the like before firing, and the firing is performed in that shape, it is of course possible to omit the pulverization step.
[0083] When the composite particles have voids at the interface between the silicon particles and the matrix phase, for example, the voids can be created at the interface between the silicon particles and the matrix phase by adding a low molecular weight organic compound when mixing with the raw material that provides the matrix phase separately from the production of the silicon slurry. The void ratio can be controlled by adjusting the amount added.
[0084] In the above-mentioned production process, the porosity of the silicon particles, the porosity of the matrix phase, and the voids at the interfaces between the silicon particles and the matrix phase are independently controlled, whereby the porosity of the composite particles can be adjusted to fall within the above-mentioned range.
[0085] In addition, the carbonaceous phase of the matrix phase of the composite particles mainly has an amorphous structure, but by controlling the sintering temperature in the manufacturing process, the interplanar spacing of the carbon 002 planes of the carbonaceous phase determined by XRD measurement can be set within the above range. For example, increasing the sintering temperature advances the carbonization reaction, narrowing the interplanar spacing of the carbon 002 planes.
[0086] When the present composite particle contains at least one element selected from the group consisting of Li, K, Na, Mg, Al, Fe, Ni, Ti and Bi, it can be produced by adding a compound containing the element when mixing the silicon slurry with the raw material that provides the matrix phase in the manufacturing method described above.
[0087] When the composite particles have the carbon coating, the composite particles having the carbon coating can be obtained by coating at least a part of the surface of the fired product obtained by the above method with a carbon coating. The carbon coating is preferably an amorphous carbon coating obtained in a chemical vapor deposition apparatus at a temperature range of 700°C to 1000°C in a flow of a pyrolytic carbon source gas and a carrier inert gas. The pyrolytic carbon source gas may be acetylene, ethylene, acetone, alcohol, propane, methane, ethane, or the like. Examples of the inert gas include nitrogen, helium, and argon, and nitrogen is usually used.
[0088] Since the present composite particle has excellent cycle characteristics, a secondary battery using the present composite particle as a secondary battery negative electrode exhibits good charge / discharge characteristics. Specifically, the composite particles can be used as a negative electrode active material, and a slurry containing an organic binder and, if necessary, other components such as a conductive assistant can be applied to a copper foil current collector as a thin film to be used as a negative electrode. A carbon material can also be added to the slurry to prepare a negative electrode. Examples of the carbon material include natural graphite, artificial graphite, and amorphous carbon such as hard carbon or soft carbon.
[0089] The present composite particles and a binder as an organic binder are kneaded together with a solvent using a dispersing device such as a stirrer, ball mill, super sand mill, or pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. The negative electrode can also be obtained by forming the paste-like negative electrode material slurry into a shape such as a sheet or pellet, and integrating it with a current collector. The negative electrode obtained by the above contains the present composite particles, and therefore becomes a secondary battery negative electrode having excellent initial coulombic efficiency. The negative electrode can be obtained, for example, by kneading the present composite particles and a binder as an organic binder together with a solvent using a dispersing device such as a stirrer, ball mill, super sand mill, or pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. The negative electrode can also be obtained by forming the paste-like negative electrode material slurry into a shape such as a sheet or pellet, and integrating it with a current collector.
[0090] Examples of the organic binder include styrene-butadiene rubber copolymers (SBR); unsaturated carboxylic acid copolymers such as ethylenically unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, and (meth)acrylic copolymers composed of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (CMC).
[0091] Depending on their physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), etc. The content of the organic binder in the negative electrode layer of the negative electrode for lithium ion secondary batteries is preferably 1% by mass to 30% by mass, more preferably 2% by mass to 20% by mass, and even more preferably 3% by mass to 15% by mass.
[0092] When the content of the organic binder is 1% by mass or more, the adhesion is better and the destruction of the negative electrode structure due to the expansion and contraction during charging and discharging is more suppressed. On the other hand, when the content is 30% by mass or less, the increase in the electrode resistance is more suppressed. Within this range, the negative electrode active material of the present invention has high chemical stability and can employ an aqueous binder, making it easy to handle in practical use.
[0093] In addition, the negative electrode material slurry may be mixed with a conductive assistant as necessary. Examples of the conductive assistant include carbon black, graphite, acetylene black, and oxides and nitrides that exhibit conductivity. The amount of the conductive assistant used may be about 1% by mass to 15% by mass with respect to the negative electrode active material of the present invention.
[0094] The material and shape of the current collector may be, for example, a strip of copper, nickel, titanium, stainless steel, etc. in the form of foil, perforated foil, mesh, etc. Also, porous materials such as porous metal (foamed metal) and carbon paper can be used.
[0095] Examples of the method for applying the negative electrode material slurry to the current collector include metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade, gravure coating, screen printing, etc. After application, it is preferable to perform a rolling treatment using a flat plate press, a calendar roll, etc., as necessary.
[0096] The negative electrode material slurry may be formed into a sheet or pellet shape, and this may be integrated with the current collector by, for example, rolling, pressing, or a combination of these.
[0097] The negative electrode layer formed on the current collector and the negative electrode layer integrated with the current collector are preferably heat-treated according to the organic binder used. For example, when a water-based styrene-butadiene rubber copolymer (SBR) is used, the heat treatment may be performed at 100 to 130°C, and when an organic binder having a polyimide or polyamideimide as the main skeleton is used, the heat treatment is preferably performed at 150 to 450°C.
[0098] This heat treatment removes the solvent, hardens the binder, and increases the strength, improving the adhesion between the particles and between the particles and the current collector. It is preferable to carry out these heat treatments in an inert atmosphere such as helium, argon, or nitrogen, or in a vacuum atmosphere, in order to prevent oxidation of the current collector during the treatment.
[0099] In addition, after the heat treatment, the negative electrode is preferably pressed (pressurized). In the negative electrode using the composite particles of the present invention, the electrode density is 1 g / cm 3 from 1.8 g / cm 3 and preferably 1.1 g / cm 3 to 1.7 g / cm 3 More preferably, it is 1.2 g / cm 3 from 1.6 g / cm 3 Regarding the electrode density, the higher the density, the more the adhesion and the volumetric capacity density of the electrode tend to improve, but if the density is too high, the voids in the electrode are reduced, weakening the effect of suppressing the volumetric expansion of silicon and the like, and the capacity retention rate decreases, so an optimal range is selected.
[0100] The negative electrode containing the composite particles has excellent cycle characteristics and is therefore suitable for use in secondary batteries. As secondary batteries having such a negative electrode, non-aqueous electrolyte secondary batteries and solid electrolyte secondary batteries are preferred, and the composite particles exhibit excellent performance when used as the negative electrode of a non-aqueous electrolyte secondary battery in particular.
[0101] When a secondary battery containing the present composite particles is used, for example, in a wet electrolyte secondary battery, it can be constructed by disposing a positive electrode and a negative electrode containing the negative electrode active material of the present invention opposite each other via a separator and injecting an electrolyte solution.
[0102] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. In this case, the current collector can be a strip of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.
[0103] There is no particular limitation on the positive electrode material used in the positive electrode layer. When manufacturing a lithium ion secondary battery among non-aqueous electrolyte secondary batteries, for example, a metal compound, a metal oxide, a metal sulfide, or a conductive polymer material capable of doping or intercalating lithium ions may be used. For example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide (LiMnO 2 ), and their composite oxides (LiCoxNiyMnzO 2 , x+y+z=1), lithium manganese spinel (LiMn 2 O 4 ), lithium vanadium compounds, V 2 O 5 , V 6 O 13 , V.O. 2 , MnO 2 , TiO 2 , MoV 2 O 8 , TiS 2 , V 2 S 5 , V.S. 2 , MoS 2 , MoS 3 , Cr 3 O 8 , Cr 2 O 5 , Olivine type LiMPO 4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, and porous carbon can be used alone or in combination.
[0104] As the separator, for example, a nonwoven fabric, cloth, microporous film, or a combination thereof, mainly composed of polyolefin such as polyethylene or polypropylene can be used. Note that if the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery to be produced are not in direct contact with each other, there is no need to use a separator.
[0105] The electrolyte is, for example, LiClO 4 , LiPF 6 , LiAsF 6 , LiBF 4 , LiSO 3 CF 3 A so-called organic electrolyte solution can be used in which a lithium salt such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, or the like is dissolved in a non-aqueous solvent of a single component or a mixture of two or more components.
[0106] The structure of the secondary battery containing the composite particles is not particularly limited, but usually, the positive electrode, the negative electrode, and a separator provided as necessary are wound into a flat spiral shape to form a wound electrode plate group, or are laminated as flat plates to form a laminated electrode plate group, and these electrode plate groups are generally sealed in an exterior body. In addition, the half cell used in the examples described below is mainly composed of the composite particles in the negative electrode, and a simple evaluation is performed using metallic lithium as the counter electrode, but this is to more clearly compare the cycle characteristics of the active material itself. It is possible to improve the cycle characteristics by adding a small amount of the composite particles to a mixture mainly composed of a graphite-based active material (capacity of about 340 mAh / g) to increase the negative electrode capacity to about 400 to 700 mAh / g, which is significantly higher than the existing negative electrode capacity.
[0107] A secondary battery containing the present composite particle is not particularly limited, and can be used as a paper-type battery, a button-type battery, a coin-type battery, a laminated battery, a cylindrical battery, a square battery, etc. The present composite particle can also be applied to all electrochemical devices that use the insertion and desorption of lithium ions as a charging and discharging mechanism, such as hybrid capacitors and solid lithium secondary batteries.
[0108] As described above, the composite particles of the present invention provide a secondary battery having excellent cycle characteristics, which is one of the important properties of a secondary battery, and therefore the composite particles of the present invention can be suitably used in secondary batteries.
[0109] Although the present composite particle, the secondary battery negative electrode having the present composite particle, and the secondary battery including the negative electrode have been described above, the present invention is not limited to the configurations of the above-described embodiments. The present composite particle, the secondary battery negative electrode having the present composite particle, and the secondary battery including the negative electrode may have any other configuration added to the configuration of the above embodiment, or may be replaced with any configuration that exhibits a similar function. EXAMPLES
[0110] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. In the half-cell used in the examples of the present invention, a simple evaluation was performed using the composite particles of the present invention as the negative electrode and metallic lithium as the counter electrode, in order to more clearly compare the cycle characteristics of the active material itself. By using such a configuration, it is possible to improve the cycle characteristics while suppressing the negative electrode capacity to about 400 to 700 mAh / g, which is much higher than the existing negative electrode capacity, by adding a small amount of the composite particles of the present invention to a mixture mainly composed of a graphite-based active material with a capacity of about 340 mAh / g.
[0111] "Synthesis Example 1: Method 1 for producing porous silicon particles" The porous silicon particles were fabricated using an anodic oxidation method. Silicon nanoparticles with a particle diameter of 100 nm were compressed into a pellet made of In and immersed in a 1.0 wt% hydrofluoric acid solution to remove the surface oxide film. The silicon particles were then introduced into an electrolytic cell and electrochemically ... 2 The electrolytic treatment was carried out for 30 minutes under constant current conditions. A Pt plate was used as the counter electrode. After electrolytic etching, the silicon particles were washed with distilled water to obtain silicon particles with a porous structure.
[0112] "Synthesis Example 2: Method 2 for producing porous silicon particles" Porous silicon particles were produced using a solution method. Silicon nanoparticles with a particle diameter of 100 nm were immersed in ethanol and subjected to ultrasonic treatment. 5 μmol of silver nitrate was added to a 0.02 M hydrofluoric acid-pure water mixed solution to form silver nanoparticles on the silicon surface. Next, a pure aqueous solution of hydrofluoric acid and hydrogen peroxide adjusted to a concentration ratio of 25:1 was added and stirred for 5 minutes to form micropores in the particles. After washing with distilled water and drying, the particles were stirred in a 1 M nitric acid solution to obtain silicon microparticles with a porous structure.
[0113] Example 1 A silicon dispersant (DISPERBYK9077: manufactured by BYK Additives & Instruments) and methyl ethyl ketone solvent were added at a mass ratio of 40% to the porous silicon particles having an average particle diameter of 100 nm prepared as in Synthesis Example 1 above, and mixed thoroughly in a stirrer to obtain a silicon slurry. A polysiloxane resin (SSA-500: manufactured by DIC Corporation) and a phenolic resin (Sumilite Resin: PR-53570, manufactured by Sumitomo Bakelite Co., Ltd.) were thoroughly mixed in a stirrer in a resin solid matter weight composition ratio of 5:5, and mixed with the silicon slurry so that the silicon element content after high-temperature firing was 50 mass%. After mixing, the solvent was removed in a nitrogen atmosphere in a 120°C oil bath, and reduced-pressure drying was performed at 110°C for 10 hours to obtain a mixed dried product.
[0114] The dried mixture was sintered at a high temperature of 1100°C for 6 hours in a nitrogen atmosphere to obtain a black sintered product. The black sintered product was pulverized in a planetary ball mill to obtain composite particles with a D50 of 6.1um. Elemental analysis was performed to calculate the silicon content of the composite particles produced, and the silicon content was 50% by mass. The silicon content was measured using an ICP-OES analyzer (Agilent5110ICP-OES, manufactured by Agilent Technologies, Inc.). The composite particles obtained as described above were further pulverized in a planetary ball mill (ball mill P-6 classic line: FRITSCH) until D50 was 1 um or less, and the true density was measured using a true density meter (Ultrapyc 5000: Anton Paar), and the specific volume was calculated from the reciprocal. The total pore volume was calculated using a specific surface area meter (Belsorp-mini X: Microtrack Bell Co., Ltd.), and the porosity of the composite particles was calculated from the following formula (1). The measurement was carried out three times, and the average porosity was 28%. Porosity (%) = total pore volume (cm 3 / g) / [total pore volume (cm 3 / g)+specific volume(cm 3 / g)] (1) The average porosity of the porous silicon particles produced in Synthesis Example 1 was also calculated by the above method and was found to be 50%.
[0115] The porosity in the matrix phase was calculated by the following method. Polysiloxane resin (SSA-500: manufactured by DIC Corporation) and phenolic resin (Sumilite Resin: PR-53570, manufactured by Sumitomo Bakelite Co., Ltd.) were thoroughly mixed in a stirrer with a resin solid matter composition ratio of 5:5. In a 120°C oil bath, the solvent was removed under a nitrogen atmosphere, and reduced pressure drying was performed at 110°C for 10 hours to obtain a mixed and dried product. The mixed and dried product was fired at a high temperature for 6 hours at 1100°C in a nitrogen atmosphere, and pulverized in a planetary ball mill until D50 was 1um or less. The true density was measured using a true density meter, and the specific volume was calculated from the reciprocal, and the total pore volume was calculated from a specific surface area meter. The porosity of the matrix phase was calculated from the above formula. The measurement was performed three times, and the average porosity was 0.1%. The average pore size was calculated using images taken with a scanning electron microscope (JEM-7200, manufactured by JEOL Ltd.) Thirty pores that could be determined to be pores were randomly selected from the 50,000x image, and the average pore size was found to be 10 nm.
[0116] A half-cell was evaluated to measure the expansion rate of the electrode. Eight parts of the composite particles, one part of the conductive additive acetylene black, and one part of an organic binder were mixed and stirred for 10 minutes with a revolution-type Awatori Rentaro (Thinky Corporation) to prepare a slurry. The organic binder was a mixture of 0.75 parts of styrene-butadiene copolymer rubber (SBR resin), 0.25 parts of carboxymethylcellulose (CMC), and 10 parts of distilled water. After applying the coating to a copper foil with a thickness of 20 μm using an applicator, the coating was dried at 110°C under reduced pressure to obtain a thin electrode film. A circular electrode with a diameter of 14 mm was punched out and pressed using a tablet press to a thickness of approximately 40 μm. The thickness was measured using a benchtop micrometer (MF-501: manufactured by Nikon Corporation) to calculate the average value of five points on the electrode.
[0117] Battery characteristics were measured using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation), and charge / discharge characteristics were evaluated under set conditions of constant current, low voltage charge / discharge, and constant current charge / discharge, with room temperature at 25°C, cutoff voltage range of 0.005 to 1.5V, and charge rate of 0.1C. The expansion rate was calculated by disassembling the battery in the initial fully charged state, cleaning the electrodes with dimethyl carbonate, air drying, and measuring the electrode thickness at five points with a thickness meter, and calculating the expansion rate using the following formula. Measurements were performed three times. The average expansion rate was 110%. Expansion rate (%) = Electrode thickness in initial fully charged state (um) / Electrode thickness before charging and discharging (um)
[0118] The full cell evaluation was performed using LiCoO as the positive electrode material. 2 A positive electrode film was prepared using a single layer sheet using aluminum foil as a positive electrode active material and a current collector, and a negative electrode film was prepared by mixing graphite powder, active material powder, and binder with a design value of 450mAh / g discharge capacity. The composition of the active material powder was adjusted so that the charge capacity of the half cell was 1500mAh / g, and a non-aqueous electrolyte solution in which lithium hexafluorophosphate was dissolved at a concentration of 1mol / L in a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1 / 1 was used as the non-aqueous electrolyte, and a laminated lithium ion secondary battery was prepared using a 30μm thick polyethylene microporous film as the separator. The laminated lithium ion secondary battery was charged at a constant current of 1.2mA (0.25c based on the positive electrode) at room temperature until the voltage of the test cell reached 4.2V, and after reaching 4.2V, the current was reduced to keep the cell voltage at 4.2V and charging was performed, and the discharge capacity was calculated. The capacity retention rate after 100 cycles at room temperature was 92%.
[0119] Examples 2 and 3 Batteries were produced in the same manner as in Example 1, except that the silicon slurry was mixed so that the silicon element content after high-temperature firing was 30 mass% in Example 2 and 70 mass% in Example 3, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0120] Example 4 2.0mA / cm 2Porous silicon was produced in the same manner as in Synthesis Example 1, except that electrolysis was performed for 5 minutes under a constant current condition of 1000 mAh. The same dispersant as in Example 1 was added at a mass ratio of 45% to the mass of the obtained porous silicon, and a methyl ethyl ketone solvent was added to form a silicon slurry. The obtained silicon slurry was mixed with the same mixture of polysiloxane resin and phenol resin as in Example 1 so that the silicon element content after high-temperature firing was 30 mass%, and a battery was produced in the same manner as in Example 1, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0121] Example 5 A battery was produced in the same manner as in Example 1, except that silicon with a particle size of 500 nm was used as the raw material, and the cycle characteristics and expansion coefficient after charge and discharge were evaluated. The results are shown in Table 1.
[0122] Example 6 A battery was produced in the same manner as in Example 1, except that silicon with a particle diameter of 1000 nm was used as the raw material and the silicon slurry was mixed so that the silicon element content after high-temperature firing was 30 mass %, and the cycle characteristics and expansion coefficient after charge and discharge were evaluated. The results are shown in Table 1.
[0123] Example 7 A battery was produced in the same manner as in Example 1, except that phenylalanine was added as a low molecular weight organic compound at a mass ratio of 20% relative to the mass of silicon when mixing the silicon slurry and resin, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0124] Example 8 2.0mA / cm 2 Porous silicon was obtained in the same manner as in Example 1, except that electrolysis was performed for 5 minutes under constant current conditions. A battery was produced in the same manner as in Example 1, except that polystyrene was added at a mass ratio of 25% to the mass of silicon when mixing the silicon slurry and resin, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0125] Example 9 The silicon slurry was mixed so that the silicon element content after high-temperature firing was 55% by mass, and when the silicon slurry and resin were mixed, 20% by mass of DISPERBYK9077 was added to the silicon mass. The battery was prepared in the same manner as in Example 1, and the cycle characteristics and expansion rate after charging and discharging were evaluated. The results are shown in Table 1.
[0126] Example 10 2.0mA / cm 2 Porous silicon was produced in the same manner as in Synthesis Example 1, except that electrolysis was performed for 40 minutes under a constant current condition of 1000 vol. m. When mixing the silicon slurry and the resin, 50 mass% of DISPERBYK9077 was added in terms of mass ratio to the silicon mass, and a battery was produced in the same manner as in Example 1, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0127] Example 11 5.0mA / cm 2 Porous silicon was obtained in the same manner as in Synthesis Example 1, except that electrolysis was performed for 15 minutes under a constant current condition of 1000 vol. m. The mass of the obtained porous silicon was added with 5% phenylalanine by mass ratio, and a methyl ethyl ketone solvent was added to form a silicon slurry. The obtained silicon slurry was mixed with the same mixture of polysiloxane resin and phenol resin as in Example 1, so that the silicon element content after high-temperature firing was 20 mass%. A battery was produced in the same manner as in Example 1, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0128] Example 12 5.0mA / cm 2 Porous silicon was obtained in the same manner as in Synthesis Example 1, except that electrolysis was performed for 15 minutes under a constant current condition of 1000 vol. m. The obtained porous silicon was used to prepare a battery in the same manner as in Example 1, except that phenylalanine was added as a low molecular weight organic compound at a mass ratio of 10% relative to the mass of silicon when mixing the silicon slurry with the mixture of polysiloxane resin and phenolic resin, and the silicon element content after high-temperature firing was 80 mass%. The cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0129] Example 13 20mA / cm 2 Porous silicon was obtained in the same manner as in Synthesis Example 1, except that electrolysis was performed for 15 minutes under a constant current condition of 100%. A battery was produced using the obtained porous silicon in the same manner as in Example 1, except that DISPERBYK9077 was added at a mass ratio of 100% relative to the mass of silicon when mixing the silicon slurry and resin, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0130] Example 14 A battery was produced in the same manner as in Example 1, except that the porous silicon produced in Synthesis Example 2 was used as the silicon, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0131] Example 15 A battery was produced in the same manner as in Example 14, except that silicon with an average particle size of 500 nm was used as the raw material, a pure aqueous solution of hydrofluoric acid and hydrogen peroxide adjusted at a concentration ratio of 25:1 was added to the silicon particles, and the silicon particles were stirred for 20 minutes to produce a slurry of silicon particles, and the silicon slurry was mixed so that the silicon element content after high-temperature firing was 70 mass%. The cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0132] Example 16 A battery was prepared in the same manner as in Example 14, except that silicon with an average particle size of 1000 nm was used as the raw material, a pure aqueous solution of hydrofluoric acid and hydrogen peroxide adjusted at a concentration ratio of 25:1 was added to the silicon particles, and the mixture was stirred for 40 minutes to prepare a slurry of silicon particles, and the silicon slurry was mixed so that the silicon element content after high-temperature firing was 50 mass%. The cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0133] Example 17 A pure aqueous solution of hydrofluoric acid and hydrogen peroxide adjusted to a concentration ratio of 25:1 was added to silicon particles, and the mixture was stirred for 10 minutes to prepare a slurry of silicon particles. A battery was prepared in the same manner as in Example 14, except that 20% by mass of DISPERBYK9077 was added to the silicon mass when the silicon slurry and resin were mixed, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0134] Example 18 A pure aqueous solution of hydrofluoric acid and hydrogen peroxide adjusted to a concentration ratio of 3:1 was added to silicon particles, and stirred for 1 minute to prepare a slurry of silicon particles. The silicon slurry was mixed so that the silicon element content after high-temperature firing was 50 mass %. Except for this, a battery was prepared in the same manner as in Example 14, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0135] Example 19 A battery was produced in the same manner as in Example 18, except that 10% by mass of polystyrene was added relative to the mass of silicon when mixing the silicon slurry and resin, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0136] Comparative Example 1 A battery was produced in the same manner as in Example 1, except that silicon particles having an average particle size of 50 nm were used, and the cycle characteristics and expansion coefficient after charge and discharge were evaluated. The results are shown in Table 1.
[0137] Comparative Example 2 20mA / cm 2Porous silicon was produced in the same manner as in Synthesis Example 1, except that electrolysis was performed for 60 minutes under a constant current condition of 1000 vol. m. The same dispersant as in Example 1 was added to the obtained porous silicon in a mass ratio of 50%, and a methyl ethyl ketone solvent was added to form a silicon slurry. The obtained silicon slurry was mixed with a mixture of the same polysiloxane resin and phenolic resin as in Example 1, so that the silicon element content after high-temperature firing was 10 mass%, and a battery was produced in the same manner as in Example 1, except that phenylalanine was added in a mass ratio of 30% relative to the silicon mass when the silicon slurry and resin were mixed, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0138] A battery was produced in the same manner as in Example 1 except that no polysiloxane resin was used, and the cycle characteristics and expansion rate after charge and discharge were evaluated. The results are shown in Table 1.
[0139] [Table 1]
[0140] The physical properties in the above examples and comparative examples were measured as follows. Average particle size: Volume average particle size (D50), measured using a laser diffraction particle size distribution measuring device (Malvern Panalytical, Mastersizer 3000).
[0141] Porosity of composite particles and silicon particles: Grinding was performed using a planetary ball mill (ball mill P-6 classic line: manufactured by FRITSCH) until D50 was 1 um or less, and the true density was measured using a true density meter, and the specific volume was calculated from the reciprocal. In addition, the total pore volume was calculated using a specific surface area meter (Belsorp-mini X: manufactured by Microtrack Bell Co., Ltd.), and the porosity of the composite particles and silicon particles was calculated from the above formula (1). The measurement was performed three times, and the average value was taken as the porosity. True density: Measured using a true density measuring device (Ultrapyc 5000 micro, manufactured by Anton Paar) with helium gas at a temperature of 25° C. and a measurement pressure of 115 kPa. Total pore volume: A specific surface area meter (Belsorp-mini X: manufactured by MicrotrackBell Co., Ltd.) was used, and nitrogen was used. The adsorption temperature was liquid nitrogen temperature (-196°C, 77K), the measurement range was 0.01-0.999 P / P0 (relative pressure), and the pretreatment conditions were 110°C under vacuum for 10 hours, after which the measurement was performed.
[0142] Porosity of matrix phase: No silicon particles were added to the raw material used to provide the matrix phase in the examples or comparative examples, and the matrix phase was prepared under the same conditions and operations as in the examples or comparative examples. The obtained matrix phase was pulverized in a planetary ball mill until D50 was 1 um or less, and the true density was measured using the same true density meter under the same conditions as above, and the specific volume was calculated from the reciprocal. In addition, the total pore volume was calculated using the same specific surface area meter under the same conditions as above. The porosity of the matrix phase alone was calculated from the above formula. The measurement was performed three times, and the average value was taken as the porosity.
[0143] Voids at the interface between silicon particles and the matrix phase: Measurement conditions were accelerating voltage 5.0 kV, irradiation current 10.0 μA, and WD: 10 nm, and calculations were performed using images taken with a scanning electron microscope (JEM-7200: manufactured by JEOL Ltd.) Fifty silicon particles were randomly selected from the 50,000x image, and the average value of the distance to the matrix layer was determined as the voids at the interface between the silicon particles and the matrix.
[0144] Average pore diameter: The measurement conditions were an acceleration voltage of 5.0 kV, an irradiation current of 10.0 μA, and a WD of 10 nm, and the calculation was performed using images taken with a scanning electron microscope (JEM-7200: manufactured by JEOL Ltd.). Thirty pores were randomly selected, and the average value of their pore diameters was taken as the average pore diameter.
[0145] Expansion rate of negative electrode: The battery in the fully charged state for the first time was disassembled, the electrodes were washed with dimethyl carbonate, and air-dried. The electrode thickness was measured at five points with a thickness gauge, and the expansion rate was calculated using the following formula. The measurement was performed three times, and the average value was used as the expansion rate of the negative electrode. Expansion rate (%) = Electrode thickness in initial fully charged state (um) / Electrode thickness before charging and discharging (um)
[0146] Battery characteristic evaluation: Battery characteristics were measured using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation), and charge / discharge characteristics were evaluated under the following set conditions: constant current, low voltage charge / discharge, and constant current charge / discharge, with a room temperature of 25°C, a cutoff voltage range of 0.005 to 1.5 V, and a charge rate of 0.1 C for the first to third charge / discharges, and 0.2 C from the fourth charge onwards. The charge rate after 10 charge / discharges was taken as the cycle characteristic.
[0147] As is clear from the above results, the secondary battery using the present composite particles has excellent cycle characteristics. The reason for this is believed to be that the composite particles have voids that exhibit a buffering effect that can sufficiently alleviate the expansion of silicon particles, since the porosity defined by the above formula (1) is within a specific range. Furthermore, it is believed that the composite particles contain silicon oxycarbide, which has excellent mechanical properties, which further suppresses the expansion of silicon particles, and also effectively utilizes the voids in the composite particles, thereby suppressing the expansion of the entire composite particle. As a result, the cycle characteristics of a secondary battery using a secondary battery negative electrode containing the composite particles were improved. This improvement effect is believed to be the result of the appropriate voids appropriately buffering the expansion of the composite particles, while suppressing the expansion rate, and suppressing the increase in surface area and the generation of SEI due to cracking.
Claims
1. A composite particle comprising a matrix phase containing silicon particles and silicon oxycarbide, having one or more voids inside the silicon particles, and an average porosity of the composite particle calculated by the following formula (1) being 1% or more and 80% or less. Porosity (%) = (total pore volume / (specific volume + total pore volume)) × 100 (1)
2. The composite particle according to claim 1 , further comprising voids at the interface between the silicon particle and the matrix phase.
3. The composite particle described in claim 1, wherein the silicon particles are porous silicon particles prepared by anodization or solution method.
4. 2. The composite particle according to claim 1, wherein the silicon particle having voids therein has a porosity calculated from the formula (1) of 10% or more and 80% or less.
5. 2. The composite particle according to claim 1, wherein a gap larger than 0 nm and not larger than 100 nm exists between the surface of at least one silicon particle and the matrix phase.
6. 2. The composite particle according to claim 1, wherein the porosity of the matrix phase calculated from the formula (1) is 20% or less.
7. 2. The composite particle according to claim 1, wherein the silicon content is from 20% by mass to 80% by mass.
8. The composite particle according to claim 1 , comprising silicon particles having a particle size of 1000 nm or less.
9. The composite particle according to claim 1 , wherein the matrix phase further comprises a carbonaceous layer.
10. A negative electrode for a secondary battery comprising the composite particle according to claim 1 .
11. A secondary battery comprising the negative electrode for secondary batteries according to claim 10.
12. A method for producing the composite particle according to any one of claims 1 to 9, comprising the steps of: Step 1: A slurry of silicon particles in which voids have been formed by anodization or a solution method is mixed with a raw material that provides a matrix phase, followed by stirring and drying to obtain a precursor. Step 2: The precursor obtained in step 1 is calcined in an inert atmosphere to obtain a calcined product. Step 3: The fired product obtained in step 2 is pulverized to obtain the present composite particles.
Citation Information
Patent Citations
Nano-composite battery electrode particles with changing properties
JP2017531907A
Electroactive materials for metal-ion batteries
JP2017533533A
Negative electrode material for battery, method for manufacturing the same, negative electrode for secondary battery, and secondary battery
JP2019125435A
Anode active material, anode containing same, and lithium secondary battery containing same
JP2019508842A
Decomposition of silicon-containing precursors onto porous scaffolds
JP2020514231A